School, Teacher and Society - Sharma, A.K. (JOURNAL OF INDIAN EDUCATION, 2011)
The lecture, being a part of the celebrations of the Golden Jubilee of the NCERT, presents a synoptic view of its notable contributions and leadership role it has played in the field of school education. It brings out that during the 50 years of the NCERT, it has been increasingly noticed for its ‘good work’ and achievements as well as for its inability to perform to expectations by the States, the school community and the public. The expectations from the NCERT’s role in school education constitute not only the dream image of NCERT but also its sub-conscious will. The lecture has been titled ‘School, Teacher and Society’ and dwells upon the symbiotic relationship of these three entities in the life of a nation. School education defines the trajectory of the young from the formative years of their growth and development to their entry into professional engagements with life. The concerns of access, equity and quality and the various ramifications of these concerns have been discussed in the context of the instrumentality of the school system to possibly minimize social inequities. The role of secondary education to produce skilled workforce for local and global requirements, for increasing GER in higher education, for increasing the productivity of both the individuals and the homes and improving the economy of the country are discussed. Quality of secondary education is dependent on the quality of the content offered at this stage of education, the manner in which transacted and evaluated, and the competencies of the teachers to communicate the same to the learners. Vocational education has not seen success as a part of secondary school education. The situation will remain static if some drastically different thinking is not done in this connection. The role of open and distance learning in enhancing the outreach of the secondary education is also discussed as a complementary alternative. Equally important are concerns of the challenges school education poses for the education of the socially deprived sections of the societies, gender disparities and curricular challenges for the physically and mentally challenged. The new responsibilities of the Boards of School Education in the context of public examinations being phased out are an issue for detailed debate. How the Guru ideal and the implications of preparing a professional teacher need to be harmonised calls for a drastic re-look at the whole modality of teacher preparation. A critical progressive ethics for teachers is oriented toward bringing out the best in all students, instead of focussing on what they are doing wrong. Rather than working from a disciplinary position, teachers generate democratic practices, whereby students and teachers collectively construct an ethical modus operandi or modus vivendi. In this humanistic vision, a genuine learning community can flourish as opposed to the market model where standards and competitiveness pit human beings against each other. A drastic overhaul of teacher education requires a serious effort and need to be initiated sooner than later. The triangular implications of School, Teacher and Society provide the framework of the various issues presented in the lecture.